Le diverse facce della montagna in declino: un’esperienza lombarda - Luisa Pedrazzini (Revue de Géographie Alpine)
The phenomenon of territories affected by obsolesce and under abandonment involves the Alpine region as a whole in several respects such as social, economic and environmental. The article aims to contribute to current studies, supporting and integrating the thesis of the complex mosaic of the Alpine space, focusing the attention in particular to the Lombardy’s mountain, where fallow lands show different characterizations, typologies and spatial structures. Taking into account the typological and territorial differences of Lombardy, the resulting picture can be considered as representative of a large part of the southern alpine face. The main typologies emerging refer to obsolete or derelict spaces because of economic or historical reasons and the relative functions were de-committed or moved elsewhere. Other cases are referred to winter resorts having lost their status due to “environmental” factors. This drives to reflect on the effects of climate change in shaping future Alpine fallow lands. The lack of snow and dramatic ice melting put in crisis local economy, with decline and recession and is the origin of great natural disasters too, causing a radical change in the way of life of the Alps’ inhabitants. This leads to the need to assess through specific scenarios the potential effects on territorial organization of the “fallow lands” that may occur due to climate change, as well as the availability of natural resources, including the effects on the economy and the consolidated life of inhabitants. This can drive to different perspectives on the use of the Alpine territory, with an alliance between disciplines to formulate tailor-made solutions including diversified, innovative purposes as well as planning preventive “rest” with scheduled “fallow lands”.